ANALISIS KUALITAS BUTIR SOAL FIQIH DAN KEMAMPUAN SISWA DI MADRASAH ALIYAH NEGERI 1 SURAKARTA - Ramadhan, Muhammad Raihan; Subando, Joko (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to produce: 1) a description of the quality of fiqh questions, 2) a description of students' abilities in working on fiqh questions, 3) a map of the level of difficulty of questions with students' abilities in working on fiqh questions at Madrasah Aliyah Negeri (MAN) 1 Surakarta. This study is an evaluation study, the components evaluated are students' abilities and the quality of the questions. The subjects of the study were 332 respondents of class XII students of Madrasah Aliyah Negeri 1 Surakarta. Data were collected using documentation techniques based on responses to final exam questions for the 2022/2023 school year in the subject of fiqh. Data analysis used the Rasch Model Theory approach with the Winstep program. The results of the study showed that 1) the inaccurate questions were items S5, S6 because they were very easy, items S12, S14, S15, S19 were detected as biased items. 2) The ability of the test participants has variations and varieties as follows: 53 students with very high abilities (16%), 12 students with high abilities (4%), 222 students with low abilities (67%) and 45 students with very low abilities (14%). 3) The level of student ability (average logit 0.06) is above the level of difficulty of the questions (average logit -0.36) meaning that in general the students' abilities exceed the level of difficulty of the questions. The results of the study recommend that valid and reliable questions can be included in the question bank while questions that are inaccurate and contain bias can be further improved.